Combined ultrasonication and thermal pre-treatment of sewage sludge for increasing methane production - Trzcinski, Antoine Prandota (2015)
This article focuses on the combination of ultrasonic and thermal treatment of sewage sludge (SS). The combination involved ultrasonicating a fraction of the sludge and thermal treatment at various temperatures and this resulted in solubilization of proteins and carbohydrates, and so contributing to increased COD solubilization. During the treatment, SCOD, soluble proteins and carbohydrates increased from 760 mg L-1 to 10,200 mg L-1, 110 mg L-1 to 2,900 mg L-1 and 60 mg L-1 to 630 mg L-1, respectively. It was found ultrasonication of only a fraction of the sludge (>20%) followed by thermal treatment led to significant improvement compared to thermal and ULS treatments applied on their own. At 65°C, the kinetic of solubilization was improved and the hyper-thermophilic treatment time could be reduced to a few hours when ultrasonication was used first. A linear correlation (R2 = 95%) was found between the SCOD obtained after ultrasonication pre-treatment and anaerobic biodegradability. The combined treatment resulted in 20% increase in biogas production during the anaerobic digestion of the pre-treated sludge.